DOP19 Myeloid and lymphoid cell abnormalities persist in the intestinal mucosa of patients who recover from COVID-19 infection. (21st January 2022) - Meringer, H; Tokuyama, M; Tankelevich, M; Martinez-Delgado, G; Jha, D; Livanos, A E; Canales-Herrerias, P; Cossarini, F; Mehandru, S
Abstract: Background: Although respiratory failure is the hallmark of severe disease, it is increasingly clear that Coronavirus Disease 2019 (COVID-19) is a multi-system disorder. The presence of gastrointestinal (Gl) involvement by Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has been suggested by epidemiological, clinical, non-human primate, in-vitro (enteroid) and ex-vivo (human biopsy) studies. Having recently documented persistence of SAR-CoV-2 within the intestinal epithelium 7 months after infection, here we aimed to study mucosal immune cell abnormalities in individuals with prior history of COVID-19. Methods: Individuals with previous COVID-19 diagnosis (by either RT–PCR or seroconversion) and controls (without RT-PCR or serological evidence of prior COVID-19 infection) undergoing endoscopic evaluation were recruited into the study (Table 1, 2). Colonic and small intestinal (duodenal and ileal) biopsies were analyzed by multiparameter flow cytometry for mucosal immune cell populations including myeloid cells (classical and non-classical monocytes, dendritic cell subsets), T cells (subsets and activation state), B cells (including plasma cells). Persistence of viral antigens was determined by immunofluorescence microscopy (n=30) using a previously published anti-nucleocapsid (NP) antibody. Results: Thirty subjects with a previous history of COVID-19 (post-COVID), median of 4 months from diagnosis (range 1–10 months), were recruited and compared with 40 normal volunteer (NV) controls. Relative to controls, post-COVID subjects displayed higher frequencies of classical (CD14 + ) monocytes in both, the colon and the small bowel, while significantly higher frequencies of conventional dendritic cells (cDC) 1 (lin - HLA-DR hi CD14 - CD11c + CD141 + ) and cDC2 (lin-HLA - DR hi CD14 -- CD11c + CD1c + ) were noted in the colon only. Among T cell subsets, CD8 + tissue resident memory T cells (CD8 + CD69 + CD103 + ) were significantly increased in colon of post-COVID subjects compared to NV. Among B cell subsets, plasma cells (CD3 - CD27 + CD38 hi ) trended higher (p=0.06), while mucosal B cells (CD3 - CD19 + ) were significantly lower in the terminal ileum of post-COVID subjects compared to NV. Finally, with IF, we detected SARS-CoV-2 NP in 10 out of 30 (33%) of post-COVID subjects (Figure 1). There were no significant correlations of these cell populations with either time after the infection or IF positivity. Conclusion: Innate and adaptive immune cell abnormalities persist in the intestinal mucosa of post-COVID subjects for up to 10 months and may reflect viral persistence or immune cell dysregulation in the intestines. These findings have major implications for understanding the pathogenesis of long term sequela of COVID-19, including long-haul COVID.